Active Learning Using Digital Smart Board to Enhance Primary School Students’ Learning - Mun, Soh Hon; Abdullah, Abdul Halim; Mokhtar, Mahani; Ali, Dayana Farzeeha; Jumaat, Nurul Farhana; Ashari, Zakiah Mohamad; Samah, Norazrena Abu; Rahman, Khairul Anuar Abdul (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Digital smart board is one of interactive technology tools which has been used widely in schools to facilitate teaching and learning. Empirical evidence shows that digital smart board allows students to construct their knowledge while mastering more advanced thinking skills. Thus integration of digital smart board facilitates active learning, which is fundamental to mastery of skills. Active learning using smart board program is a program which integrates smart board in Data Handling so that primary school students can learn Data Handling concept actively and meaningfully. Therefore, this study was conducted to identify the effectiveness of active learning using smart board program to enhance primary school students’ learning. Five experts in teaching Mathematics Education and thirty year five students were involved in this study. The students were selected based on purposive sampling. This study used both quantitative and qualitative research approach. A set of interview protocol and a set of questionnaire were used during the data collection phase. Findings from the questionnaire were analysed based on descriptive and inferential statistics by using Winsteps Version 3.72.3. In addition, thematic analysis was used to analyse the qualitative data. Findings from the study indicate that active learning using smart board program has the attributes which can effectively enhance primary school students’ learning. It is hoped that the results from this study can contribute towards development of active learning strategies, methods or activities using smart board in order to enhance primary students’ learning in school.